THE IMPLEMENTATION EFFECTIVENESS OF HOSPITAL RESPONSIBILITY TOWARDS MEDICAL DISPUTE PROCESS AT HOSPITAL X CIBINONG - Adelin Litan; Fresley Hutapea; Rina Mutiara (Jurnal Ilmiah Teunuleh, 2021)
Medical disputes that are rife in the medical world in Indonesia are a separate burden for medical personnel in carrying out daily practices, where the hospital as a place for medical personnel to work, should be responsible for medical personnel involved in medical disputes. The absence of sufficiently clear regulations governing the responsibility of hospitals in resolving medical disputes, makes medical personnel, in this case, the most disadvantaged part. The purpose of this study is to empirically determine the applicable laws and regulations regarding the responsibility of hospitals in the process of resolving medical disputes and the effectiveness of their implementation. The research method used is qualitative research with case study approach. Data sources are primary and secondary data. The data analysis subjects were informants, namely the director of medical services, the legal department officer and the public relations officer. The analysis tool uses interactive analysis. There were at least 4 laws and regulations related to hospital responsibility for medical personnel and implementation of regulations regarding hospital responsibility towards medical dispute process is 88%. The research found no guidelines for handling medical disputes. This study shows that the laws and regulations related to hospital responsibility and their implementation in the medical dispute resolution process have been implemented. The recommendation to Hospital X Cibinong is to make guidelines on the flow of medical dispute handling and provide education about health law to all hospital staff, especially medical personnel as parties most vulnerable to malpractice suits.